Elastic thickness structure of South America estimated using wavelets and satellite-derived gravity data - Tassara, A.; Swain, Christopher; Hackney, R.; Kirby, Jonathan (Elsevier Science BV, 2007)
We used a wavelet formulation of the classical spectral isostatic analysis to invert satellite-derived gravity and topography/bathymetry for elastic thickness (Te) over South America and its surrounding plates. To provide a homogeneous representation of the gravity field for this vast region, we corrected free-air anomalies derived from a combination of terrestrial/marine gravity data with data from the GRACE and CHAMP satellite missions (model EIGEN-CG03C) by a simple Bouguer slab using a smoothed representation of surface relief (wavelengths > 125 km). The resulting Bouguer anomaly compares well with terrestrial data acquired in the Central Andes and allows Te to be confidently estimated for values greater than 10 km. The Te map resolves regional-scale features that are well-correlated with known surface structures and shows maximum values of 10015 km over theArchean?Neoproterozoic core of the continent, decreasing to less than 30 km around continental margins. Several regions of the oceanic plates and continental margins have an elastic thickness less than 10 km. We performed a quantitative analysis by comparing the elastic thickness with the thermal structure predicted from the age of oceanic crust and igneous?metamorphic rocks. This demonstrates that oceanic plates have been weakened by thermal interaction with hotspots and locally by fracturing and hydration near the trench. We observe that only the nucleus of the continent has resisted the thermomechanical weakening induced by the rifting of Africa and South America along the passive margin and the Andean orogeny along the active margin. This latter region shows along-strike variations in Te that correlate with the geotectonic segmentation of the margin and with the pattern of crustal seismicity. Our results reveal that the rigidity structure follows the segmentation of the seismogenic zone along the subduction fault, suggesting a causal relationship that should be investigated in order to improve the understanding and predictability of great earthquakes and tsunamis.